The Effect of Budgetary Participation, Budget Emphasis, and Compensation on Budgetary Slack at Ayodya Resort Bali - N K Dwiandriani; I M M Arsana; I M Suarta (Jurusan Akuntansi Politeknik Negeri Bali, 2019)
The directors and managers at Ayodya Resort Bali participated in company budgeting and were pressured to be able to achieve budgeting target, therefore, the directors and managers simplified budgeting target achievement through budgetary slack to gain compensation in the form of bonus. This study aimed to know the effect of budgetary participation, budget emphasis and compensation on budgetary slack both partially and simultaneously at Ayodya Resort Bali. The type of data used in this study was primary data obtained through distributing questionnaire to the respondents consisted of the directors of each department and the managers of each section per department at Ayodya Resort Bali. The sampling methods used in the study were saturated sampling technique for all directors and simple random sampling technique for the managers. The data were analyzed by using simple linear regression analysis and multiple linear regression analysis. The results of the study showed that: (1) Budgetary participation had a significant positive effect on budgetary slack. (2) Budget emphasis had a significant positive effect on budgetary slack. (3) Compensation had a significant positive effect on budgetary slack. (4) Budgetary participation, budget emphasis and compensation stimultanouesly had a significant positive effect on budgetary slack. This suggests that increased participation in budgeting followed by negative behavior and high emphasis on achieving the target budget for compensation will tend to increase the occurrence of budgetary slack.